Development of village information system website as a strategy for increasing the tourism experience in Sindangresmi village - Pamungkas, Fajar Triaji; Virgono, Agus; Hasibuan, Faisal Candrasyah (Universitas Telkom, 2025)
Tourism is an important function in increasing the regional economy. In recent years, digitization has emerged as a transformative force in the tourism industry, providing new possibilities for enhancing the tourist experience and making development sustainable. Sindangresmi Village, located in Central Jampang, has a unique cultural heritage, natural landscapes, and culture attractive to tourists. However, to remain competitive in the current tourism scene, embodying virtual technologies to provide the land with immersive and engaging stories is important. Digital systems can facilitate the involvement and empowerment of networks in tourism development. Online networks and social media companies can serve as a channel of communication for residents, enabling them to share their stories, traditions, and entrepreneurship with tourists. This virtual connection fosters experiences of satisfaction and encourages sustainable tourism practices that maintain the cultural heritage and tourism of the village. The digitization of tourism provides a wide opportunity for Sindangresmi Village to enhance its tourism experience. By leveraging digital advertising and marketing techniques, immersive technologies, intelligent control structures, and internet engagement systems, villages can attract more visitors and enhance the tourism experience. Using digitalization is important for Sindangresmi Village to develop a dynamic tourism aspect while maintaining its distinctive identity and heritage.